War and Peace : Relationships between Hmong and Chinese - Yang, Chee (My University, 2013)
The purpose of this study was to learn about the relationship between the Hmong and the Chinese. Specifically, the relationship between the Han and Hmong and use of the term Miao.
Color poster with text, maps, and photographs.
Keywords: Han Chinese; Hmong-Chinese relations; Posters